The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/3679145
|View full text |Cite
|
Sign up to set email alerts
|

A Vehicle Path Planning Algorithm Based on Mixed Policy Gradient Actor‐Critic Model with Random Escape Term and Filter Optimization

Abstract: The transportation system of those countries has a huge traffic flow is bearing great pressure on transportation planning and management. Vehicle path planning is one of the effective ways to alleviate such pressure. Deep reinforcement learning (DRL), as a state-of-the-art solution method in vehicle path planning, can better balance the ability and complexity of the algorithm to reflect the real situation. However, DRL has its own disadvantages of higher search cost and earlier convergence to the local optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Moreover, the model has assigned different memory weights to different memory-forgetting durations based on human memory characteristics [67]. Nai et al have proposed a hybrid policy gradient-based actor-critic generative adversarial RL model to describe the route choice strategies and optimization methods for micro travelers [68]. Zhao et al have proposed a universal deep inverse reinforcement learning (IRL) framework for link-based route choice modeling, which combines different features of state, action, and travel context and captures the dynamic properties of micro route choice, achieving competitive interpretability of micro travel decision-making [69].…”
Section: Models With Information Factors Consideredmentioning
confidence: 99%
“…Moreover, the model has assigned different memory weights to different memory-forgetting durations based on human memory characteristics [67]. Nai et al have proposed a hybrid policy gradient-based actor-critic generative adversarial RL model to describe the route choice strategies and optimization methods for micro travelers [68]. Zhao et al have proposed a universal deep inverse reinforcement learning (IRL) framework for link-based route choice modeling, which combines different features of state, action, and travel context and captures the dynamic properties of micro route choice, achieving competitive interpretability of micro travel decision-making [69].…”
Section: Models With Information Factors Consideredmentioning
confidence: 99%
“…Li et al [34] proposed an DRL method based on an attention mechanism, which contains a vehicle selection decoder considering heterogeneous fleet constraints and a node selection decoder considering route construction. Nai et al [35] proposed a mixedstrategy gradient actor-critic model with a stochastic escape term and a filtering operation, using a model-driven approach to ensure the convergence speed of the whole model. Berat et al [36] proposed a synergistic combination of deep reinforcement learning and hierarchical game theory as a modelling framework for driver behaviour prediction in motorway driving scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…Data has shown that China's urbanization process has been continuously accelerating, at the end of the year 2021, the urbanization rate of China's resident population has reached up to 64.72% [1]. In the expanding scale of large and medium-sized cities, limited urban transportation resources and increasing transportation demand have formed a significant supply-demand contradiction [2]. It is very important to achieve effective governance of urban transportation and solve congestion problems as much as possible, and such effective governance relies on a deep understanding of the rules of urban transportation travel.…”
Section: Introductionmentioning
confidence: 99%